2004
DOI: 10.1007/s00330-004-2339-8
|View full text |Cite
|
Sign up to set email alerts
|

Early modifications of hepatic perfusion measured by functional CT in a rat model of hepatocellular carcinoma using a blood pool contrast agent

Abstract: Macromolecular contrast-enhanced functional CT was performed to characterize early perfusion changes in hepatocellular carcinoma (HCC). Fourteen rats with chemically induced primary liver tumors ranging pathologically from hyperplasia to HCC and 15 control rats were investigated. Two dynamic CT scans using an experimental macromolecular contrast agent were performed on a single slice 11 and 18 weeks after tumor induction followed by pathological examination. A deconvolution mathematical model was applied, yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 16 publications
(29 reference statements)
1
39
0
1
Order By: Relevance
“…In addition, many CT perfusion analyses were performed using a single arterial input [8,9,15] , but the liver has a dual arterial-portal blood supply, and the tumor and portal vein could not be consistently included. In our study, 64-rows multi-detector CT was introduced to offer a greater coverage (up to 4 cm), thus overcoming this limitation by including both the tumor and portal vein in dual-input analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, many CT perfusion analyses were performed using a single arterial input [8,9,15] , but the liver has a dual arterial-portal blood supply, and the tumor and portal vein could not be consistently included. In our study, 64-rows multi-detector CT was introduced to offer a greater coverage (up to 4 cm), thus overcoming this limitation by including both the tumor and portal vein in dual-input analysis.…”
Section: Discussionmentioning
confidence: 99%
“…CT examination after TACE has been widely used to assess the efficacy of TACE [6] , but its limitation is that a quantitative evaluation cannot be provided and an incomplete lipiodol accumulation may disturb the assessment of viable tumors on contrastenhanced CT imaging [7] . Alternatively, CT perfusion imaging is a non-invasive technique for assessment of tissue perfusion in locally advanced HCC [8][9][10] . The response to TACE may be evaluated by comparing the difference in perfusion parameters pre-and post-treatment [11,12] .…”
Section: Introductionmentioning
confidence: 99%
“…Fabiano et al [10] and Wang et al [11] also have found differences between the values of the CT p parameters of benign and malignant liver lesions. Fournier et al [12] have previously identified differences in CT p values between regenerative and dysplastic carcinomatous nodules, which allowed early detection of HCC. Tsushima et al [13] have performed a comparative study to evaluate CT p of HCC and liver metastases of colorectal origin.…”
Section: Discussionmentioning
confidence: 99%
“…The timeattenuation curve (TAC) over the tissue or organ of interest is used, with various models of single-and multiple-compartment flow, to estimate parameters such as absolute blood flow and volume and vascular permeability (1)(2)(3). For oncologic applications, increased tissue perfusion has been studied to assess tumor malignancy and potential response to therapy, while in ischemic disease applications, blood flow is correlated to tissue viability (1,(4)(5)(6)(7). Thus, CT perfusion imaging may have a clinical role in both oncologic and cardiovascular applications.…”
Section: Discussionmentioning
confidence: 99%